Hepatic fibrinogen storage disease: identification of two novel mutations (p.Asp316Asn, fibrinogen Pisa and p.Gly366Ser, fibrinogen Beograd) impacting on the fibrinogen γ‐module. (14th July 2015) - Asselta, R.; Robusto, M.; Braidotti, P.; Peyvandi, F.; Nastasio, S.; D'Antiga, L.; Perisic, V. N.; Maggiore, G.; Caccia, S.; Duga, S.
Summary Background Quantitative fibrinogen deficiencies (hypofibrinogenemia and afibrinogenemia) are rare congenital disorders characterized by low/unmeasurable plasma fibrinogen antigen levels. Their genetic basis is invariably represented by mutations within the fibrinogen genes (FGA, FGB and FGG coding for the Aα, Bβ and γ chains). Currently, only four mutations (p.Gly284Arg, p.Arg375Trp, delGVYYQ 346‐350, p.Thr314Pro), all affecting the fibrinogen γ chain, have been reported to cause fibrinogen storage disease (FSD), a disorder characterized by protein aggregation, endoplasmic reticulum retention and hypofibrinogenemia. Objectives To investigate the genetic basis of FSD in two hypofibrinogenemic patients. Methods The mutational screening of the fibrinogen genes was performed by direct DNA sequencing. The impact of identified mutations on fibrinogen structure was investigated by in‐silico molecular modeling. Liver histology was evaluated by light microscopy, electron microscopy and immunocytochemistry. Results Here, we describe two hypofibrinogenemic children with persistent abnormal liver function parameters. Direct sequencing of the coding portion of fibrinogen genes disclosed two novel FGG missense variants (p.Asp316Asn, fibrinogen Pisa; p.Gly366Ser, fibrinogen Beograd), both present in the heterozygous state and affecting residues located in the fibrinogen C‐terminal γ‐module. Liver sections derived from biopsies of the two patients were examined by immunocytochemical analyses, revealing hepatocyte cytoplasmic inclusions immunoreactive to anti‐fibrinogen antibodies. Conclusions Our work strongly confirms the clustering of mutations causing FSD in the fibrinogen γ chain between residues 284 and 375. Based on an in‐depth structural analysis of all FSD‐causing mutations and on their resemblance to mutations leading to serpinopathies, we also comment on a possible mechanism explaining fibrinogen polymerization within hepatocytes.